Performance of Automatic Watering System for Bean Sprout Based on Microcontroller ATmega 328p - Muhammad Idkham; Siti Mechram; Danang Abiyyudanah; Wirda Syadara; Muhammad Dhafir; Syafrizal Syafrizal (The University of Lampung, 2025)
Technological advancements in agriculture are crucial to meeting the increasing global food demand. Mung bean sprout (Vigna radiata) cultivation requires efficient irrigation to ensure optimal growth. This study designs and evaluates an automatic irrigation system based on the ATmega 328P microcontroller to address the challenge of watering every four hours. The system integrates water flow sensors, relays, and solenoid valves controlled by C-based software in the Arduino IDE. Nine different irrigation test combinations were conducted to determine the most effective strategy. Each treatment had three levels and was tested in triplicate. Data analysis was performed using ANOVA (α = 0.05), followed by the DMRT test to evaluate treatment interactions. Results indicate that the system operates consistently in regulating water flow, improving irrigation efficiency, and reducing human intervention. The best performance was achieved using 50 liters of water with a shower nozzle, yielding the highest production capacity. The system improves irrigation efficiency, prevents over- and under-watering, and enhances crop yield. Analysis shows that water quantity and spraying method influence the yield ratio value in a complex pattern. The W2N3 combination produced the highest value (3.6), while W1N1 had the lowest (2.4). Overall, their interaction significantly affects irrigation effectiveness. Keywords: Agricultural automation, Automatic irrigation, Microcontroller ATmega 328P, Mung bean sprouts (Vigna radiata), Performance testing.